2016
DOI: 10.1097/bpo.0000000000000448
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Comprehensibility of Physical Activity Scales for Children With Sport Injuries

Abstract: Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 19 publications
0
18
1
Order By: Relevance
“…Several studies showed that these questionnaires are valid, reliable and responsive in adult patients with a variety of knee disorders [35]. However, recent studies showed that the adult versions of the IKDC and KOOS are inappropriate for use in children due to a lack of comprehensibility [6]. Subsequently, the child friendly Pedi-IKDC and KOOS-Child were developed and validated [79].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that these questionnaires are valid, reliable and responsive in adult patients with a variety of knee disorders [35]. However, recent studies showed that the adult versions of the IKDC and KOOS are inappropriate for use in children due to a lack of comprehensibility [6]. Subsequently, the child friendly Pedi-IKDC and KOOS-Child were developed and validated [79].…”
Section: Introductionmentioning
confidence: 99%
“…While the Tegner is used to accurately categorize activity in adults and adolescents, this study showed that it cannot effectively differentiate the activity level of pediatric athletes. Iversen et al 17 reported that 87% of children had difficulty distinguishing the various levels used in the Tegner, as various sports are repeated. For example, soccer and football are repeated in both Tegner level 9 and level 10; relying on the ability of the respondent to select a level with no provided directions yielded inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…The behavioral scientist then trained the interviewer in cognitive interviewing procedures and techniques (AF), until he was deemed proficient in the interview process. This protocol has been utilized in multiple previous studies [33, 34, 39, 40].…”
Section: Methodsmentioning
confidence: 99%